Medium optimization for β-galactosidase production by a thermotolerant yeast - Sirinda Am-Aiam (2018)
© 2015, Chiang Mai University. All rights reserved. Kluyveromyces sp. CK8 was previously isolated from rotten fruit in northern Thailand and found to be capable of growing at 45°C. This research aimed to identify the yeast isolate and to optimize its production of β-galactosidase in synthetic medium using lactose as the sole carbon source. Molecular identification via phylogenetic analysis, based on comparative sequence analysis of the 26S rRNA gene at the D1/D2 domain, revealed that isolate CK8 was Kluyveromyces marxianus. The yeast isolate produced β-galactosidase 5.33 U/ml culture when cultivated at 37°C for 18 h in Yeast-Malt extract (YM) medium containing 1% (w/v) lactose as the sole carbon source. Optimization of medium composition for enzyme production was conducted using 2-Level Factorial experimental design to determine the most relevant variables of the culture medium composition. Among five parameters, yeast extract, (NH4)2SO4 and KH2PO4 were significant effectors at p<0.05. A central composite design (CCD) and response surface plot predicted the highest β-galactosidase activity of 8.94 U/ml culture in the medium containing (g/l) of the following: yeast extract (0.23), (NH4)2SO4 (9.64), KH2PO4 (7.0), lactose (20) and MgSO4.7H2O (0.1). A validation time course culture study conducted for 18 h in the optimal medium found that the actual maximum value of enzyme activity was 8.82 U/ml culture which is 98.66% of the predicted value.